If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=n-6/2
We move all terms to the left:
2-(n-6/2)=0
We add all the numbers together, and all the variables
-(n-3)+2=0
We get rid of parentheses
-n+3+2=0
We add all the numbers together, and all the variables
-1n+5=0
We move all terms containing n to the left, all other terms to the right
-n=-5
n=-5/-1
n=+5
| 13x-20x=1/3 | | 8g=8+10g | | 2y^2-7=0 | | -1-7f=5-9f | | 7-6s=-5-6s | | 3k+6=4k | | 12z=10z+20-12 | | 12x-7x=2x+5 | | 7=7+1/10t | | -6x+6(2x+-3)=-5-7x | | 0.2/b=20 | | -4m+3m=3/2 | | x^2+(x–4)^2=20^2 | | 3y^2-11y+12=0 | | 9(2e+1)-3(e-2)=45 | | (x+-8)^4=16 | | -5j=4j-9j | | x^2+13+24=0 | | -q+10=5q-8 | | 9×(x-2)=3x×(x-2) | | 3n-1=3n | | 9(x-1)=90 | | x+√4x+1=5 | | 7(3x-1)/4=-14 | | 2z-4=2z+3 | | 4(2u+8)=5(u+4) | | 7(3x-1)=-14 | | -4c=6c-10 | | −13(23x+5)=−43(12x−8) | | (2/5)+(2/x)=1 | | 9a-8-6=-27 | | -3(1+5x)+1=-107 |